REFERENCE TO EXAMPLES OF FOLK ORAL CREATIVITY IN CHOLPON’S WORK - Ahmadjonova , Muslimakhon (Educational Research in Universal Sciences, 2023)
In this article, the artistic and aesthetic significance of the examples of the oral creation of the character found in Cholpon’s work, and their place in his work will be explained.